TATA KELOLA PERUSAHAAN DAN RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - YOHANNA ROSA ANGELINE; RUDI SETIADI TJAHJONO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The aim of this study is to obtain empirical evidence about the effect of corporate governance (audit committee, size of the commissioner’s board, proportion of independent commissioner’s board), firm size, and financial ratio (leverage, liquidity, activity, profitability) to firm value. Sample used in this study are all manufacturing companies listed in Indonesia Stock Exchange consistently during the period from 2015 until 2017. Sample selection method used was purposive sampling, there were 69 companies met the criteria, resulting 207 data are taken as sample. Research data were analyzed by doing hypothesis test using multiple regression method to determine the model of research. The results of this study show that proportion of independent commissioner’s board, leverage, and profitability affect firm value. Audit committee, size of the commissioner’s board, firm size, liquidity, and activity have no effect to value of the firm.